TRAINING OF TEACHERS AT FAREL EDUCATION CENTRE AND PRIMA QUANTUM TUTORING IN USING GEOGEBRA - Mira Gusniwati; Nia Gardenia; Andri Rahadyan; Indra Kurniawan; Muslihatul Hidayah; Halimatussa'diah Halimatussa'diah (Universitas Muhammadiyah Mataram, 2020)
Low results from studying mathematics at the Farel Education Center and the Prima Quantum tutoring can indicate a poor understanding of mathematical concepts among students. This community service activity aims to provide additional insights to teachers as participants in media and mathematics learning aids using the GeoGebra application. Teachers' ability to understand mathematical concepts can be improved to help students understand mathematics more effectively. Participants in this community service activity were the Farel Education Center for Teachers and the Prima Quantum tutoring in Jakarta. There are three phases of action: the preparation, implementation, and evaluation to implement this Community service activity. Observation, documentation, and demonstration are the method of execution of this community service activity. The result of this community service activity was that teachers at Farel Education Center and Prima Quantum tutoring who initially did not know the GeoGebra application and its benefits can now take advantage of GeoGebra in their learning. It can increase motivation, interest in education, student creativity, and understanding of mathematics.